Perinatal excellence to reduce injury in preterm birth (PERIPrem) through quality improvement. Issue 3 (9th August 2022) - Glover Williams, Alessandra; Tuvey, Sam; McBain, Hayley; Menzies, Noshin; Hedge, Sally; Bates, Sarah; Luyt, Karen
Abstract : Perinatal Excellence to Reduce Injury in Premature Birth (PERIPrem) is an 11-element perinatal care bundle designed to improve outcomes for preterm babies, in line with the National Health Service (NHS) Long Term plan. Designed in collaboration with 12 NHS Trusts (secondary care hospitals), South West and West of England Academic Health Science Networks, South West Neonatal Operational Delivery Network, parent partners and clinical experts, implementation was via bespoke quality improvement (QI) methodology. Before project initiation, there was regional variation in uptake of elements, evidenced by baseline audit. Optimisation of the preterm infant is complex; eligibility for treatments is dependent on gestation and local policies. Preterm infants experience variability in care dependent on the place of birth, and there remains an implementation gap for several effective, evidence-based treatments. The PERIPrem ambition is to reduce severe brain injury and death caused by prematurity by at least 50% through the delivery of a perinatal care bundle. The PERIPrem approach resulted in improved element implementation by 26% (from 3% to 29%) between 2019 and 2021, with dyads significantly more likely to receive the full bundle in 2021 compared with 2019 (probability=0.96 (95% CI 0.87 to 0.99), p<0.001). When examining the impact on psychological safety and team-working of PERIPrem, linear mixed models indicated an improvement in team function (p=0.021), situation monitoring (p=0.029) and communication within teams (p=0.002). Central to success was the development of a committed multiorganisational collaborative that continues to drive perinatal improvement using a common language and streamlining processes. In addition to saving the lives of the most vulnerable babies, PERIPrem aims to improve the chances of disability-free lives and is successfully nurturing high-functioning perinatal teams with enhanced QI skills.